The confidence of undergraduate dental students when performing root canal treatment and their perception of the quality of endodontic education. (9th December 2014) - Davey, J.; Bryant, S. T.; Dummer, P. M. H.
Abstract Aim This article aims to gain understanding into the perception of undergraduate dental students in terms of their confidence and competence at performing root canal treatment and their perception of the quality of endodontic education. Methods An online questionnaire was distributed to all 3rd, 4th and 5th year dental students at Cardiff University via their academic e‐mail addresses. The questionnaire utilised both scaled response and open questions to gain an insight into undergraduate opinion. Results Out of a possible 208 students, 98 responses were obtained (response rate = 47%). Perception of competence and confidence were significantly greater amongst the more senior year groups (P < 0.01). However, 49% (n = 38) of participants did not feel competent performing root canal treatment on anterior, single‐rooted teeth, whilst 74% (n = 70) did not feel competent performing root canal treatment on posterior, multirooted teeth. Free comments from participants indicated that this was due to a lack of clinical experience. Approximately, 80% of participants ranked education in endodontics at Cardiff University as ≤5 on a Likert scale (1 = inadequate to 10 = good), indicating that improvement was required. Improvements that were suggested by the students included the provision of further information within lectures, a broader range of lecturers, an increased number of shorter, more organised practical sessions, additional training equipment, greater supervision and online reference guides to root canal treatment. Conclusion Enhancing undergraduate education in endodontics is necessary to increase students' perception of their confidence and competence when performing root canal treatment.